Characterization of the Terra Nova Bay Polynya Using Dual-Polarimetric C-Band SAR Measurements - Inserra G.; Buono A.; Nunziata F.; Migliaccio M.; Parmiggiani F.; Aulicino G. (IEEE Journal of Oceanic Engineering, 2024)
In polar regions, coastal polynyas are key drivers for climate since they represent the primary source of ice mass production and oceanic circulation. In this study, multipolarization C-band synthetic aperture radar (SAR) measurements acquired by the Radarsat-2 satellite mission are exploited to observe the Terra Nova Bay (TNB) coastal polynya in the Ross Sea, Antarctica. Incoherent and coherent features, extracted from dual-polarimetric SAR measurements, are used to characterize the TNB coastal polynya under different environmental conditions. The analysis is also supported, when available, by independent optical remote sensing information collected by the thermal infrared channels of the moderate resolution imaging spectroradiometer and by ancillary on-site information about wind and air temperature collected by automatic weather stations. Experimental results show that the SAR plays a key role in providing information about the TNB polynya thanks to its fine spatial resolution and its almost continuous imaging capabilities. In addition, dual-polarimetric SAR offers unprecedented opportunities with respect to single-polarization SAR in performing accurate and unsupervised classification of the area within the polynya. Hence, a more accurate estimation of the polynya extent and the fractional area coverage of sea water within the polynyas obtained.